CSF HIV RNA Escape in Opsoclonus-Myoclonus-Ataxia Syndrome: Case Report and Review of the Literature - Cabaraux, Pierre; Poncelet, Arthur; Honnorat, Jérome; Demeester, Remy; Cherifi, Soraya; Manto, Mario (Frontiers in Neurology, 2020)
Background : HIV infection is associated with a broad range of neurological manifestations, including opsoclonus-myoclonus ataxia syndrome (OMAS) occurring in primary infection, immune reconstitution syndrome or in case of opportunistic co-infection. Background : Human immunodeficiency viruses (HIV) infection is associated with a broad range of neurological manifestations, including opsoclonus-myoclonus ataxia syndrome (OMAS) occur- ring in primary infection, immune reconstitution syndrome or in case of opportunistic co-infection. Case : We report the exceptional case of a 43-year-old female under HIV treatment for ten years who presented initially with suspected epileptic seizure. Although the clinical picture slightly im- proved under anti-epileptic treatment, it was rapidly attributed to OMAS. The patient exhibited marked opsoclonus, mild dysarthria, upper limbs intermittent myoclonus, ataxia in 4 limbs, truncal ataxia and a severe gait ataxia (SARA score: 34). The diagnostic work-up showed radiological and biological signs of central nervous system (CNS) inflammation and cerebral venous sinus throm- boses. The HIV viral load was higher in cerebrospinal fluid (CSF) than in the blood (4560 copies/ ml versus 76 copies/ml). She was treated for 5 days with pulsed corticotherapy. Dolutegravir and anticoagulation administration were initiated. Follow-ups at 2 and 4 months showed a dramatic im- provement of clinical neurologic status (SARA score at 4 months: 1), reduction of CNS inflamma- tion and revealed undetectable CSF and serum viral loads. Conclusion : This case underlines the importance of the evaluation of the CSF viral load in HIV patients developing OMAS and suggests CSF HIV RNA escape as a novel cause for OMAS